2013
DOI: 10.1002/ls.1236
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐viscosity behaviour and film thickness in elastohydrodynamic regime of lubrication of ionic liquids and other base oils

Abstract: Viscosities at high pressures for 16 base oils (six polyolesters, three polyglycols, six ionic liquids and squalane) were used to analyze the influence of their chemical structure on the pressure‐viscosity coefficient, α. Comparisons with literature α values for vegetable bases (canola, soybean and jojoba oils) are also performed. For the molecular lubricants, we found trends that are coherent with the literature, whereas for ionic liquids (ILs), new trends were found. ILs based on tris(pentafluoroethyl)triflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 58 publications
(187 reference statements)
2
20
0
Order By: Relevance
“…In general, the compressibility of ILs is much lower than that of standard hydraulic mineral oils and even lower than that of water [3] in several cases under broad temperature and pressure conditions. Besides, in previous papers [16][17][18][19] we have found that most of the ILs analysed have low pressure-viscosity coefficients in comparison with most of the conventional lubricants. According to Mia and Ohno [20], high bulk modulus fluids having low pressure-viscosity coefficient, indicate an efficient hydraulic fluid.…”
Section: Introductionmentioning
confidence: 77%
“…In general, the compressibility of ILs is much lower than that of standard hydraulic mineral oils and even lower than that of water [3] in several cases under broad temperature and pressure conditions. Besides, in previous papers [16][17][18][19] we have found that most of the ILs analysed have low pressure-viscosity coefficients in comparison with most of the conventional lubricants. According to Mia and Ohno [20], high bulk modulus fluids having low pressure-viscosity coefficient, indicate an efficient hydraulic fluid.…”
Section: Introductionmentioning
confidence: 77%
“…The dispersion of graphene in ILs has been shown to achieve enhanced tribological performance [6,15,[18][19][20][21]. The rheological study of ionic liquids, nanofluids and dispersions is an important aspect for their practical applications, particularly as thermal fluids and lubricants or lubricant additives [22].…”
Section: Introductionmentioning
confidence: 99%
“…5 ILs feature several favorable characteristics that can prevent those undesired situations, including high thermal stability, non-flammability, negligible volatility, and appropriate pressure-viscosity and temperatureviscosity dependence. 3,[5][6][7] ILs were also suggested as lubricants in spatial applications owing to their low vapor pressure and high radiation resistance properties. 8 They were as well considered in lubricated systems for their use as additives 3 or with additives 5 and can exhibit in both cases better responses than usual lubricants.…”
Section: Introductionmentioning
confidence: 99%